A COMPARATIVE STUDY OF USING CLASSWIDE PEER TUTORING TECHNIQUE AND ‎STUDENT TEAM ‎ ACHIEVEMENT DEVISION TECHNIQUE IN ‎ TEACHING READING COMPREHENSION AT STATE SENIOR HIGH SCHOOL ‎ ‎1 TUALANG‎ - Erika, Sumita (Journal of Education and Teaching, 2021)
The purpose of this study was to explore which strategy that required a teacher for a better learning process in improving students’ reading comprehension in the eleventh grade at state senior high school Tualang. It was done based on experimental design which focused on the quantitative research group. A group were taken as experimental groups and a group as the comparison group. The sample consisted of 60 students that were taken from the eleventh grade at state senir high school Tualang which were comprised of 30 students from XI-4class for this experimental group 1  (Classwide Peer Tutoring Technique), 30 students from XI-5 class for this experimental group 2 (Student Team Achievement Technique).Observation sheets and reading comprehension tests were used in the study. There are 40 items of multiple choice questions used for the pre-test and post-test.  To analyze the data, independent sample t-test were calculated by using SPSS 20 with a significant probability of Ho was accepted if P<0.05 or there was no significant effect after giving the treatments, Ha was accepted if P>0.05 or there was no significant effect after giving the treatments. Classwide Peer Tutoring Technique got the effect size or eta-squared as follows: Eta-squared = 0.84x 100% = 84%. Student Team Achievement Technique got the effect size or eta-squared as follows: Eta-squared = 0.91 x 100% = 91%. The highest effect was from Student Team Achievement Technique, but the two classes did not differ significantly. Therefore, the two strategies could improve the students’ reading comprehension.